Spontaneous recognition of impactful video games: a user-centric classification framework - Terron-Lopez, Pilar; Terrón-López, María-José; Castilla-Cebrian, Guillermo (Frontiers in Computer Science, 2024)
The potential impact of a video game is directly conditioned by its recognizability in the public concience.. But classifying video games in this manner can be a challenging endeavor. This paper emphasizes inconsistencies in recognition metrics and the absence of a unified system of classification. It approches the problem through a twofold methodology involving a systematic literature review exploring existing classifications and genres, and an exploratory survey gathering data on spontaneously recognized video games in Spain. The study utilizes quantitative data to create three lists of video games-most played globally, most representative internationally, and most significant in the Spanish market. The findings reveal complexities in comparing video game data and underscore the importance of comprehensive research frameworks. The study contributes valuable insights into video game recognition dynamics among users, addresses the scarcity of comparative research in the gaming field, revealing the subjective impact of globally recognized video games and highlighting the possible relations between industry trends, spontaneous recognition, and consumer preferences.